2011
DOI: 10.1080/10410236.2010.544283
|View full text |Cite
|
Sign up to set email alerts
|

Empathic Exchanges in Online Cancer Support Groups: Distinguishing Message Expression and Reception Effects

Abstract: Past studies on the efficacy of participation in online cancer support groups have primarily focused on the role of expression in the accrual of health benefits for participants. Unfortunately, few steps have been taken to determine whether this observed effect arises solely from the internal mental processes underlying the act of expressing or, perhaps, owes something to a nuanced, multidimensional understanding of expression that includes reception of responses to what is expressed. To test for the multilaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(129 citation statements)
references
References 36 publications
(62 reference statements)
2
127
0
Order By: Relevance
“…Information exchange was rare in this online support community and other online communities without empathic support. 39,54 However, more research attention needs to be paid to Internet support for patients with lung cancer, and especially their support persons, as there are few studies identifying their experiences and outcomes in peer-led online support communities, as well as ''when'' in the illness trajectory they are seeking information exchange and empathic support. 52 The messages analyzed in this study came primarily from females who were wives or daughters of the patient and females diagnosed with lung cancer.…”
Section: Naturalistic Conversationsmentioning
confidence: 98%
“…Information exchange was rare in this online support community and other online communities without empathic support. 39,54 However, more research attention needs to be paid to Internet support for patients with lung cancer, and especially their support persons, as there are few studies identifying their experiences and outcomes in peer-led online support communities, as well as ''when'' in the illness trajectory they are seeking information exchange and empathic support. 52 The messages analyzed in this study came primarily from females who were wives or daughters of the patient and females diagnosed with lung cancer.…”
Section: Naturalistic Conversationsmentioning
confidence: 98%
“…Previous studies by Shaw et al (2006, 2007) have found that breast cancer patients who post about their experience can have a range of psychosocial benefits. More recent work suggests that it is the mental processes underlying the actual composition of language that produces the benefits (Han et al, 2011; Pennebaker, 1997). Expression’s health benefits may in fact not be effects of disclosure in the literal sense of revealing pre-existing memory contents.…”
Section: Lurking As An Active Participation Processmentioning
confidence: 99%
“…As illustrated in Fig. 2, this merged data can be combined with longitudinal survey data collected before and after a support group intervention to examine why some patients express and/or receive more [33] and how expression and reception relate to psychosocial health outcomes for patients [32]. This methodological approach could provide highly granular data on the nature of the exchanges occurring within online support groups and offer an avenue to exploring effects previously inaccessible for testing due to the limits of extant research methodologies.…”
Section: Message Expression and Reception Effectmentioning
confidence: 96%
“…Han et al [32] used the MySQL relational database management system to combine the content coding of individual messages with another database generated from log data. Log data contained information about individual participants' online handle and numerical ID, the message relevant behavior (i.e., post, read), and the message ID related to posting or reading.…”
Section: Message Expression and Reception Effectmentioning
confidence: 99%